A spatiotemporal analysis of e-scooters' relationships with transit and station-based bikeshare. (December 2021) - Yan, Xiang; Yang, Wencui; Zhang, Xiaojian; Xu, Yiming; Bejleri, Ilir; Zhao, Xilei
Abstract: To address the policy question of how e-scooters interact with existing public mobility options, we conduct a spatiotemporal analysis of e-scooters' relationships with public transit and station-based bikeshare in Washington DC. Results suggest that e-scooters have both competing and complementary effects on transit and bikeshare. The service areas of the three modes largely overlap, and most e-scooter trips could have been made by transit or bikeshare. A travel-time-based analysis further reveals that when choosing e-scooters over transit, travelers pay a price premium but save some travel time. The price premium was greater during COVID-19 but the associated travel-time savings were smaller. This implies that public health considerations rather than time-cost tradeoffs were the main determinant of travel behavior during COVID-19. In addition, we find that e-scooters enhance mobility services for some underserved neighborhoods. Before COVID-19, about 10% of all e-scooter trips were taken to connect with the Metrorail system. Highlights: A spatiotemporal analysis of e-scooter availability and use in Washington DC. The supply of e-scooters overlaps with the service areas of transit and bikeshare. Travelers pay a price premium and save time when choosing e-scooters over transit. E-scooters enhance mobility for several underserved neighborhoods. About 10% of e-scooter trips are taken to connect with metro services.